Effects of Fasting on Plasma and Platelet-Free Fatty Acids and Platelet Function in Healthy Males - Gjesdal, Knut; Nordøy, Arne; Wang, Harald; Berntsen, Harald; Mjøs, Ole D. (Thrombosis and Haemostasis, 1976)
10 healthy male volunteers fasted for 72 hours. Their plasma concentration of free fatty acid increased more than two-fold, to 1.8 mmol/1. The number of reversible venous “in vivo” platelet aggregates increased significantly (p <0.01); this figure correlated with the concentration of long-chain saturated free fatty acid in plasma (p <0.02). The correlation with the amount of long-chain saturated free fatty acid plus oleic acid (18:1) was even better (p <0.01). Plasma PF-4 concentration increased, suggesting increased platelet release reaction. In spite of the plasma increase, total platelet FFA concentration was reduced and there was a change in the distribution of platelet free fatty acid which correlated with the degree of aggregation.